Atomistic basis for the on–off signaling mechanism in SAM-II riboswitch - Kelley, Jennifer Munro (Oxford University Press, 2010)
Many bacterial genes are controlled by metabolite sensing motifs known as riboswitches, normally located in the 5′ un-translated region of their mRNAs. Small molecular metabolites bind to the aptamer domain of riboswitches with amazing specificity, modulating gene regulation in a feedback loop as a result of induced conformational changes in the expression platform. Here, we report the results of molecular dynamics simulation studies of the S-adenosylmethionine (SAM)-II riboswitch that is involved in regulating translation in sulfur metabolic pathways in bacteria. We show that the ensemble of conformations of the unbound form of the SAM-II riboswitch is a loose pseudoknot structure that periodically visits conformations similar to the bound form, and the pseudoknot structure is only fully formed upon binding the metabolite, SAM. The rate of forming contacts in the unbound form that are similar to that in the bound form is fast. Ligand binding to SAM-II alters the curvature and base-pairing of the expression platform that could affect the interaction of the latter with the ribosome.